1995
DOI: 10.1136/thx.50.7.755
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive mechanical ventilation in acute respiratory failure due to chronic obstructive pulmonary disease: correlates for success.

Abstract: Background -Non-invasive mechanical ventilation is increasingly used in the treatment of acute respiratory failure in patients with chronic obstructive pulmonary disease (COPD). The Non-invasive mechanical ventilation is increasingly being used in the treatment of acute respiratory failure in patients with chronic obstructive pulmonary disease (COPD). To date, controlled studies comparing non-invasive mechanical ventilation with endotracheal intubation are lacking, so the use of non-invasive mechanical venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
203
7
13

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(244 citation statements)
references
References 11 publications
21
203
7
13
Order By: Relevance
“…However, these results are only achieved if NIV is set properly and the patient9s acceptance and tolerance of the procedure are optimal. Several clinical studies have reported that lack of compliance to ventilation is one of the major causes of failure in both acute hypercapnic and pure hypoxic respiratory failure [26][27][28].…”
Section: Tolerance To Ventilation and Air Leaksmentioning
confidence: 99%
“…However, these results are only achieved if NIV is set properly and the patient9s acceptance and tolerance of the procedure are optimal. Several clinical studies have reported that lack of compliance to ventilation is one of the major causes of failure in both acute hypercapnic and pure hypoxic respiratory failure [26][27][28].…”
Section: Tolerance To Ventilation and Air Leaksmentioning
confidence: 99%
“…Thus it would appear that only a minority of failures of NIPSV could be related to major difficulties in the application of the technique. It is likely that failures of the method are more often due to the severity of the acute respiratory failure as demonstrated by AMBROSINO et al [25], and especially to the lack of rapid improvement in blood pH [4,6,21,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…However, pneumonia in patients treated with NIV is persistently associated with poor outcome in the literature, compared with other causes of ARF, both in patients with COPD exacerbations (29) and in hypoxemic ARF (28). More recent studies have confirmed high failure rates in patients with pneumonia and severe ARF (27,(30)(31)(32).…”
Section: Severe Community-acquired Pneumoniamentioning
confidence: 97%